Global Sensing and Sensibility: A Multi-Stage Matching Assessment of Competitive Advantage from Foreign Sources of Innovation - Thorsten Teichert; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
We focus on one of the core competitive capabilities of modern firms: the ability to deliver successful innovations in a globalized environment. Companies literally find themselves confronted with a world of ideas. The challenge remains to decide which impulses should be on top of the list and which at the bottom. Given limited resources and substantial investments, betting on the wrong horse can be risky and costly. Theoretically integrated in capability based view of the firm we investigate firms? capabilities to assimilate, identify and prioritize valuable knowledge across national, cultural and social borders - a competence we call global sensing. We establish an analytical framework to examine whether global sensing activities generate competitive advantage. Consequently, we develop an empirical, multistage evaluation strategy. This strategy rests on a matching approach for a recent, broad sample of almost 1,700 German companies from both services and manufacturing. We find the strongest and most consistent support for global sensing as a strategic enabler for technological leadership. Apart from this strategic advantage we observe that foreign external sources of innovation are generally not superior to domestic ones.
Keywords: F23; O31; O32; 330; Global innovation; global sensing; capability based view; matching estimation; Innovationswettbewerb; Internationaler Wettbewerb; Multinationales Unternehmen; Wissenstransfer; Technologieprognose; Frühwarnsystem; Globalisierung; Schätzung; Deutschland